P2‐K0.75[Ni1/3Mn2/3]O2 Cathode Material for High Power and Long Life Potassium‐Ion Batteries. Issue 7 (12th January 2020) - Jo, Jae Hyeon; Choi, Ji Ung; Park, Yun Ji; Jung, Young Hwa; Ahn, Docheon; Jeon, Tae‐Yeol; Kim, Hyungsub; Kim, Jongsoon; Myung, Seung‐Taek
Abstract: Rationally designed P2‐K0.75 [Ni1/3 Mn2/3 ]O2 is introduced as a novel cathode material for potassium‐ion batteries (KIBs). P2‐K0.75 [Ni1/3 Mn2/3 ]O2 cathode material designed through electrochemical ion‐exchange from P2‐Na2/3 [Ni1/3 Mn2/3 ]O2 exhibits satisfactory electrode performances; 110 mAh g −1 (20 mA g −1 ) retaining 86% of capacity for 300 cycles and unexpectedly high reversible capacity of about 91 mAh g −1 (1400 mA g −1 ) with excellent capacity retention of 83% over 500 cycles. According to theoretical and experimental investigations, the overall potassium storage mechanism of P2‐K0.75 [Ni1/3 Mn2/3 ]O2 is revealed to be a single‐phase reaction with small lattice change upon charge and discharge, presenting the Ni 4+/2+ redox couple reaction. Such high power capability is possible through the facile K + migration in the K0.75 [Ni1/3 Mn2/3 ]O2 structure with a low activation barrier energy of ≈210 meV. These findings indicate that P2‐K0.75 [Ni1/3 Mn2/3 ]O2 is a promising candidate cathode material for high‐rate and long‐life KIBs. Abstract : Rationally designed P2‐K0.75 [Ni1/3 Mn2/3 ]O2 exhibits stable cycle life at high rates. Structural insights into the K‐ion de/intercalation mechanism is elucidated through combined theoretical and experimental studies. A single phase reaction activated by Ni 4+/2+ contributes to the long term cycling stability over 500 cycles at high rates.